Faktor-Faktor yang Berhubungan dengan Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Jetis 1 Bantul - Widya, Wastu; Adzka Fahma Rodliya (Lembaga Pengembangan Kinerja Dosen, 2023)
Stunting is a condition of growth failure in infants that occurs during a critical period of the process of growth and development in the womb and during the initial period after the baby is born. It is not only affected the physical growth of the baby but also the brain. The purpose of this research was to determine the factors associated with the stunting prevalence among the children under five years old of age in Jetis 1 Primary Health Care Center, Bantul. The research method is quantitative, case control research design with retrospective approach. The data analysis methods were chi-square and logistic regression. The results of this research were some factors could be associated with stunting prevalence. The factors were the history of exclusive breastfeeding (p: 0.037 or: 0.253) and the nutritional status of the mother during pregnancy (p: 0.001 or: 5.634). Meanwhile, gender (p: 0.153), history of birth weight (p: 0.677) and mother's education (p: 0.127) were found to have no relationship with stunting prevalence. It is expected that the mothers of children under five years old can prepare for pregnancy in the future by calculating nutritional intake before and during pregnancy and provide exclusive breastfeeding for 6 months.